Analysis of the use of special tax treatment for agricultural companies - I. Khairullina, Olga (2019)
The importance of further development of the agricultural sector of economy and solution of tasks set for it necessitated the study of a single agricultural tax as a preferential treatment for agricultural companies. We analyzed the dynamics of investments and taxes, their relationship. We determined that investments are sensitive to any changes taking place in the economy. At the same time, one of the prerequisites for their growth shall be effective tax incentives in the form of benefits and preferences for agriculture. We also analyzed the practical use of the special tax treatment - a single agricultural tax. We determined the advantages and disadvantages of the application of SACT in Russian practice. We found that large companies do not fully use this preferential treatment. The structure of tax payments shows that the most significant is the payment of social taxes, which occupy 62%. In this regard, we gave recommendations on updating this treatment for the agricultural companies in Russia.